The Relationship Between Employability Skills on Accounting Graduate Employability - Daud, Norhaslinda Binti; Poad, Muhammad Akmal Arif Bin Mohd (International Journal of Research in Interdisciplinary Studies, 2025)
The growing intricacy and requirements of the contemporary job market have amplified the significance of employability skills for accounting graduates. These graduates must possess essential employability skills, including effective communication and problem-solving abilities. The objective of this study is to examine the relationship between employability skills on the employability of accounting graduates. It offers valuable insights into the impact of these abilities and qualities on employability outcomes, aiding in shaping educational methods and enhancing graduates' preparedness for the job market. Building upon previous research, this study particularly examines the experiences of accounting graduates who encounter distinct problems and have specific expectations in the professional environment. Although employability skills are crucial, there is a significant lack of information in the literature about the specific ways in which these abilities affect the success of accounting graduates. This study aims to fill this gap by examining data gathered from accounting graduates and utilising pearson correlation to comprehend the connections between the indicated abilities and employability. The results demonstrate substantial positive relationships between communication skills and employability, underscoring the significance of these qualities in the field of accounting. Problem-solving skills exhibit different levels of impact, indicating the necessity for a nuanced strategy in cultivating these talents within educational programs. The study's results highlight the importance of curriculum developers, educators, and policymakers prioritising key employability skills in accounting education. This study contributes to the overall comprehension of how employability skills might improve career outcomes for accounting graduates, providing practical suggestions for both educational institutions and companies.